Phylogenomic reconstruction reveals new insights into the evolution and biogeography of Atta leaf-cutting ants (Hymenoptera: Formicidae) - Barrera, Corina A. [UNESP]; Sosa-Calvo, Jeffrey; Schultz, Ted R.; Rabeling, Christian; Bacci, Maurício [UNESP] (My University, 2022)
Atta Fabricius is an ecologically dominant leaf-cutting ant genus, the major herbivore of the Neotropics, and an agricultural pest of great economic importance. Phylogenetic relationships within Atta have until now remained uncertain, and the delimitation and identification of a subset of Atta species are problematic. To address these phylogenetic uncertainties, we reconstruct the most comprehensive phylogenetic estimate to date of Atta by employing ultraconserved elements (UCEs). We recovered 2340 UCE loci from 224 Atta specimens, which include 14 out of the 15 identifiable species from across their geographic distributions, and 49 outgroup specimens. Our results strongly support the monophyly of Atta and of the four clades that coincide with the previously recognized subgenera Archeatta Gonçalves, Atta s.s. Emery, Epiatta Borgmeier, and Neoatta Gonçalves. The Archeatta clade contains three species occurring in North and Central America and the Caribbean and is the sister group of the remainder of all other Atta species. The Atta s.s. clade is composed of two species occupying North, Central, and South America. The Epiatta clade contains seven entirely South American species and the two species of the Neoatta clade occur in Central and South America. Divergence-dating analyses identify a series of major events in the Miocene, such as the divergence of Acromyrmex Mayr and Atta 16.7 million years ago (Ma) and the crown-group origin of Atta around 8.5 Ma. Extant Atta species evolved very recently, originating in the early Pleistocene, approximately 1.8–0.3 Ma (crown-group ages). We provide the first evidence that Atta goiana Gonçalves belongs to the Epiatta clade and that Atta robusta Borgmeier is the species with the youngest crown-group age of 0.3 Ma. The very young ages of Atta and its component species indicate a recent, rapid radiation. Biogeographic analyses suggest that the range of the most recent common ancestor of Atta consisted of the combined North/Central America and NW South America bioregions and that one daughter lineage subsequently dispersed into South America, rapidly diversifying in the newly formed Cerrado biome and Chaco, and further dispersing into the Atlantic Forest, Caatinga, and Pampas bioregions.